Cardiac energy metabolic disorder and gut microbiota imbalance: a study on the therapeutic potential of Shenfu Injection in rats with heart failure - Zhao, Zhenyu; Hu, Zhixi; Li, Lin (Frontiers in Microbiology, 2025)
ObjectiveTo investigate the relationship between heart failure (HF) and gut microbiota-mediated energy metabolism, and to explore the role of Shenfu Injection in this process.Materials and methodsIn this study, Adriamycin-induced chronic heart failure (CHF) rat model was used and randomly divided into the blank control group (Normal, n = 9), HF control group (Model, n = 12), Shenfu Injection treatment group (SFI, n = 9), and positive drug control group (TMZ, n = 9). The changes in gut microbiota structure were analyzed by 16S rRNA high-throughput sequencing, the content of short-chain fatty acids (SCFAs) was detected by targeted metabolomics technology, and cardiac function and energy metabolism-related indicators were evaluated.ResultsMyocardial energy metabolism in HF rats was disordered, characterized by reduced fatty acid oxidation, enhanced anaerobic glycolysis of glucose, mitochondrial damage, and decreased ATP content; The gut microbiota of HF rats was imbalanced, with a reduction in beneficial bacteria, an increase in conditional pathogenic bacteria, and impaired intestinal barrier function; Both Shenfu Injection and trimetazidine improved myocardial energy metabolism and cardiac function, but Shenfu Injection was more significant in regulating gut microbiota and improving intestinal health; The production of SCFAs from the gut microbiota of HF rats increased, which may be closely related to myocardial energy metabolism; SCFAs-producing bacteria Akkermansia and Blautia played a key role in the development of HF, and their abundance was positively correlated with SCFAs content.ConclusionShenfu Injection in treating HF may improve myocardial energy metabolism and intestinal health by regulating gut microbiota, especially the abundance of SCFAs-producing bacteria Akkermansia and Blautia, thereby exerting therapeutic effects. This provides theoretical support for treatment strategies based on gut microbiota.